2020
DOI: 10.1186/s42523-020-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance gene sharing networks and the effect of dietary nutritional content on the canine and feline gut resistome

Abstract: Background: As one of the most densely populated microbial communities on Earth, the gut microbiota serves as an important reservoir of antibiotic resistance genes (ARGs), referred to as the gut resistome. Here, we investigated the association of dietary nutritional content with gut ARG diversity and composition, using publicly available shotgun metagenomic sequence data generated from canine and feline fecal samples. Also, based on network theory, we explored ARG-sharing patterns between gut bacterial genera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
3
21
2
Order By: Relevance
“…The genes abundant in juvenile included those that are involved in fatty acid biosynthesis, phenylalanine metabolism, purine metabolism, glutathione metabolism, antibiotic resistance, and biosynthesis of streptomycin in the shooting stage [ 4 ]. The dietary nutritional content, especially protein content, was previously found associated with the abundance of ARGs in the gut [ 25 ]. Besides milk, bamboo shoots are a good protein source with protein content ranging from 1.49 g/100 g to 4.04 g/100 g in fresh bamboo shoots [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes abundant in juvenile included those that are involved in fatty acid biosynthesis, phenylalanine metabolism, purine metabolism, glutathione metabolism, antibiotic resistance, and biosynthesis of streptomycin in the shooting stage [ 4 ]. The dietary nutritional content, especially protein content, was previously found associated with the abundance of ARGs in the gut [ 25 ]. Besides milk, bamboo shoots are a good protein source with protein content ranging from 1.49 g/100 g to 4.04 g/100 g in fresh bamboo shoots [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet is an essential factor that may influence the gut microbiome [ 20 24 ]. Increased antibiotic resistance genes (ARGs) have been observed with a high protein diet in a recent study [ 25 ]. Another study revealed a varying rate of expression of genes involved in phenylalanine metabolism, fatty acid biosynthesis, purine metabolism, glutathione metabolism, antibiotic resistance, and streptomycin biosynthesis in the gut of juvenile GPs that were fed with bamboo leaves and shoot as diet and the more genes were found in shooting stage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent review, β-lactams such as amoxicillin are the most commonly used antimicrobials for dogs and cats in European countries including UK, Italy, and four Nordic countries [ 221 ]. A recent study investigated the profiles of resistome in the digestive tract of dogs and cats and found that tetracycline and aminoglycoside resistance genes were the most abundant among the 23 classes of ARGs, indicating that the gut microbiota of dogs and cats is also a reservoir of ARGs [ 222 ]. We thus speculate that there could be many shared ARGs between these companion and food-producing animals living together in farms considering the similarity of the profiles of predominant ARGs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This selective pressure can enrich antimicrobial resistance genes (ARGs), which can be rapidly disseminated and exchanged between bacteria via horizontal gene transfer of mobile genetic elements (MGEs) or through de novo mutations that are positively selected ( 16 18 ). In the intestinal tract of humans and animals, there is evidence that antibiotic use can enrich multiple ARGs in not only gut pathogens, but also commensals ( 4 , 19 22 ).…”
Section: Introductionmentioning
confidence: 99%